Analysis of factors influencing postoperative hand function in DEB with hand deformities - Xinhe JIAO; Yuluo JIAN; Lu WANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective: To investigate the influencing factors of postoperative hand function in patients with dystrophic epidermolysis bullosa. Methods: A retrospective analysis was performed in 41 patients with dystrophic epidermolysis bullosa with hands contractures deformities. According to the hand function scores 2 years after surgery, patients were classified into unrestricted hand function and restricted hand function groups. Basic conditions, use of postoperative hand braces and other common factors were compared between the two groups to determine the influencing factors of postoperative hand function. Results: According to hand function scores, subjects with unrestricted hand function and restricted hand function were 20 and 21 patients, respectively. There were no significant differences in age, gender, race, BMI, BARTHEL index, nutritional status, hemoglobin concentration, blood glucose and coagulation function between the two groups (P>0.05), while there were significant differences in the use of hand support between the two groups (χ2=12.95, P<0.05). Conclusion: The application of hand brace after surgical treatment is an important factor that affects the postoperative hand function in patients with dystrophic epidermolysis bullosa hands complicated with contracture deformities.